Inmigrantes. Del estado de excepción al estado de derecho (Immigrants. From the State of Siege to the Rule of Law) - Javier De Lucas (Oñati Socio-Legal Series)
The evolution of migration policies in the EU shows that the so-called "spirit of Tampere" and especially the objectives of full integration, understood as a mutual negotiation process, governed by the principle of equality in all rights and the priority of the rule of law, suffer an increasing deterioration, under the double pretext of economic crisis and the withdrawal securitarian. The alternative proposed by Lochak seems clearer than ever and growing concern about particular orientation Juridical (Legislative more than case law) that is tilted by the logic of "state of siege. " Against this, there is a renewed focus on the one hand, the minimum that represents respect for the principles and rules of the rule of law, but also the need to place on the political agenda of the EU mechanisms to make accessible the citizenship for immigrants